(untitled) - Ellis, Rod (Oxford, 1997)
This book outlines the study of how people learn a language other than their mother tongue. It is designed to make the essentials of this rapidly expanding field as accessible as possible.
Keywords: Language and languages; Study and teaching; Rresearch